Identification of suitable flavonoids as insulin degrading enzyme inhibitors through in-silico approach - Saranya Dharmaraj, Preeya Negi, M. Esakkimuthukumar, Akey Krishna Swaroop, S. Jubie (Journal of Applied Pharmaceutical Science, 2023)
The present work is aimed to identify the inhibitors for insulin-degrading enzyme (IDE) from plant secondary metabolites through in-silico studies. IDE is a protease that cleaves insulin and other bioactive peptides such as amyloid-β. IDE is the important drug target for diabetes because IDE is the principal insulin-degrading protease in vivo, IDE inhibitors should enhance insulin signaling and thus have efficacy in relevant animal models of diabetes and also in therapy. The in-silico absorption distribution metabolism elimination screening was carried out to find out the drug likeness properties of selected flavonoids. In-silico molecular docking simulations have been performed to positional phytoconstituents into the preferred binding site of the protein receptor IDE, to predict the binding modes, the binding affinities and the orientation of all ligands. The docking studies revealed that all compounds showed good docking score. In-silico molecular docking simulations have been performed to positional phytoconstituents into the preferred binding site of the protein receptor IDE, to predict the binding modes, the binding affinities and the orientation of all ligands. The docking studies revealed that all compounds showed good docking score. The prediction of the binding affinity of a new compound to an identified target is a significant parameter in the development of a new drug. It is found that the flavonoids quercetin, genistein, wogonin, isorhamnetin and luteolin had drug like properties rutin and Diosmin are in good bioavailability radar and diosmin, wogonin and flavilium elicit a higher binding affinity with IDE.